Changes in the Composition of the Northern Polar Upper Stratosphere in February 2009 After a Sudden Stratospheric Warming - Cordero-Carrasco, R; Damiani, A (Wiley-Blackwell, 2014)
Variability in the chemistry of the upper stratosphere/lower mesosphere region has been analyzed focusing on high latitudes during the boreal winter in 2009 characterized by the strong sudden stratospheric warming (SSW) on 24 January. Data from Michelson Interferometer for Passive Atmospheric Sounding aboard Envisat and the Microwave Limb Sounder on Aura have been used to exemplify these changes. Record high (low) values of O3 and ClO (temperature and HCl) for the winters of 2005–2012, coupled with a simultaneous enhancement of ClONO2, have been observed in February 2009. This suggests that the very low temperatures favor a more effective ozone production and a greater O3/O ratio. The latter is the main factor controlling active chlorine partitioning. Increases of ClO lead to high ClONO2 concentrations in the upper stratosphere at high latitudes, where its photodissociation rate is smaller. Since this increase of ClONO2 happens at the expense of HCl, the region of high ClONO2 roughly coincides with the region of low HCl. Although this period was characterized by an elevated stratopause event, the investigated region was not influenced by the descent of mesospheric air rich in NOx. Some limited enhancements in NOx at ~1 hPa occurred at latitudes greater than 80°N after about 20 February, but they became consistent only in March. Intrusion of midlatitude air mostly occurred between the SSW and early February. Then, the sum of volume mixing ratios of ClONO2 +ClO+HCl remained approximately constant and close to the values of the other years. In contrast, it was up to 0.2 ppbv lower during the SSW period. These atypical chemical conditions occurred also in February 2006, but 2009 stands out for its long-lasting effects, which persisted until late March. © 2014. American Geophysical Union. All Rights Reserved.